Miner Artist/Minor Artist? Class, Politics, and the Post-industrial Consumption of Mining Art - Spence, Jean (Frontiers in Sociology, 2020)
This article uses the recently discovered art work of a County Durham miner, Jimmy Kays (1886-1951) to highlight the terms in which mining art has achieved popularity and value in the post-mining period. Kays work will be analysed with reference to the presenting narrative that promotes and markets mining art not only in terms of its intrinsic artistic quality, but also with regard to a particular interpretation of the mining past. The surviving artwork of Jimmy Kays, has not, and can not achieve a similar status and as such sits outside the lexicon of mining art. I suggest that an understanding of the public invisibility of art work such as that produced by Kays illuminates the exercise of class-based power in terms of the production, consumption and range of meaning inscribed within mining art. The argument suggests that the mining art that has been allocated value is in danger of being appropriated in ways that pacify rather than energise audiences, by emphasising the sentimental and nostalgic over what might be political and contentious aspects of memorialising.